PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENDEKATAN MATEMATIKA REALISTIK PADA OPERASI HITUNG DI KELAS I SD UNGGUL TERPADU PADANG PARIAMAN - Januarti Januarti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
At grade I SD Unggul Terpadu Padang Pariaman, teacher used to teach mathematics traditionally. This study is aimed to improve students’ learning achievement by implementing Realistic Mathematics Education approach. This is a classroom action research consisting of planning, implementation, observation, and reflection. Data were collected through observation, interview, and test. In cycle, average score of students’ learning achievement is 77.2 and become 88.2 in cycle II. Hence, Realistic Mathematics Education can improve students’ learning achievement.